Vazayif-i Danishgah-i Kummunisti-i Zahmat'kashan-i Sharq : (Danishjuyan-i Havadar-i Sazman-i Paykar dar Rah-i Azadi-i Tabaqah'-i Kargar)
'The positions of communist universities and labourers in the Iestern countries'